Speed Synchronization of web winding System with Sliding Mode Control - Hachemi Glaoui; Abdeldejbar Hazzab; Bousmaha Bouchiba; Ismaïl Khalil Bousserhane (Institute of Advanced Engineering and Science, 2013)
A continuous web winding system is a large-scale, complex interconnected dynamic system with numerous tension zones to transport the web while processing it. There are two control schemes for large-scale system control: the centralized scheme and the decentralized scheme. Centralized control is the traditional control method, which considers all the information about the system to be a single dynamic model and design a control system for this model. A speed synchronization control strategy for multiple induction motors, based on adjacent cross-coupling control structure, is developed by employing total sliding mode control method. The proposed control strategy is to stabilize speed tracking of each induction motor while synchronizing its speed with the speed of the other motors so as to make speed synchronization error amongst induction motors converge to zero. The global stability and the convergence of the designed controller are proved by using Lyapunov method. Simulation results demonstrate the effectiveness of the proposed method.DOI: http://dx.doi.org/10.11591/ijpeds.v3i2.2432